Hubungan Dukungan Keluarga Dengan Kepatuhan Pengobatan Pasien Tuberkulosis Di Poli Paru RSUD Kota Tanjungpinang - Sugeng Rahayu; Elvi Murniasih; Fitriani Suangga (Lembaga Pengembangan Kinerja Dosen, 2024)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. India is ranked 3rd with the highest number of TB sufferers in the world after India and China. Globally, it is estimated that 9.9 million people suffer from TB in 2020. The total number of TB cases that have been discovered and treated (Treatment Coverage) in the Riau Islands Province in 2021 is 5,055 cases. This study aims to determine the relationship between family support and treatment compliance in Tuberculosis patients at the Pulmonary Polyclinic, Tanjungpinang City Hospital. This research design is descriptive quantitative with a cross sectional approach. A sample of 46 respondents was selected using the Purposive Sampling sampling technique. Data were processed using the Chi-Square test. Univariate data was obtained for the variable